ANALISIS PERBANDINGAN KINERJA PERUSAHAAN MELALUI RASIO KEUANGAN PADA PERUSAHAAN INDUSTRI MAKANAN - Sastrawan, Rahman; Pratiwi, Nia; Lestari, Siti; Azmi, Ika Nur (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the performance of companies in the food industry, namely: Indofood CBP Sukses Makmur Tbk (ICBP), Indofood Sukses Makmur Tbk (INDF), Mayora Indah Tbk (MYOR), Nippon Indosari Corpindo Tbk (ROTI), and Garudafood Putra Putri Jaya Tbk (GOOD) for the period 2022-2024 using financial ratios through liquidity, solvency, activity and profitability parameters. This research method is quantitative descriptive, research data in the form of company financial reports for the period 2022-2024. The results of the study show that the analysis of company performance with financial ratios through liquidity ratio parameters can be concluded that the company with the ICBP code has the best company performance in the last three years (2022-2024). Judging from the solvency ratio, activity ratio, and profitability ratio, the best company performance in the last three years (2022-2024) is the company with the ROTI code. Every company must increase its assets, sales and reduce its debt or liabilities, so that the company's performance can be better.